Effect of the Ramathibodi Rapid Response System Triggered by the Ramathibodi Early Warning Score and Clinical Warning Signs on in-Hospital Mortality and the Incidence of Cardiopulmonary Resuscitation in Adult Hospitalized Patients - Kwantong C; Sutherasan Y; Junhasavasdikul D; Petnak T; Theerawit P (Dove Medical Press, 2023)
Chutipong Kwantong,1 Yuda Sutherasan,2 Detajin Junhasavasdikul,2 Tananchai Petnak,2 Pongdhep Theerawit3 1Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 2Division of Pulmonary and Pulmonary Critical Care Medicine, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Division of Critical Care Medicine, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Yuda Sutherasan, Division of Pulmonary and Pulmonary Critical Care Medicine, Department of Medicine, Faculty of Medicine Ramathibodi Hospital, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, Thailand, Tel +6622011619, Fax +6622011629 Ext 2, Email Sutherasan_yuda@yahoo.comPurpose: The Ramathibodi Rapid Response System (RRRS), implemented in March 2017, aims to identify and respond to patients with deteriorating conditions outside the ICU. It employs the Ramathibodi early warning score and clinical signs to monitor all admitted patients, providing expert physician monitoring and early treatment for stabilization and appropriate care triage. This study assesses the RRRS's effectiveness in reducing in-hospital mortality and CPR events outside the ICU.Patients and Methods: We conducted a retrospective observational study from March 2014 to February 2020 in a tertiary care hospital's general wards. We included adult patients experiencing unplanned ICU admission, sudden cardiac arrest, or unexpected death. The study compared in-hospital mortality and CPR incidence outside the ICU between pre- and post-RRRS implementation groups. The associations between RRRS implementation and in-hospital mortality and the incidence of CPR outside the ICU were assessed using multiple logistic regression analyses.Results: We evaluated 17,741 admissions, with 9168 before RRRS implementation (1 March 2014 to 28 February 2017) and 8573 after RRRS implementation (1 March 2017 to 29 February 2020). The implementation of RRRS was associated with a significant reduction in in-hospital mortality, which decreased from 30.0% to 20.8% (odds ratio, 0.62; 95% confidence interval [CI], 0.57 to 0.66; P< 0.0001). Even after adjusting for age, sex, and comorbidities, the reduction in in-hospital mortality remained significant (adjusted odds ratio, 0.58; 95% CI, 0.54 to 0.63; P< 0.0001). The incidence of CPR outside the ICU also decreased from 1.8% to 1.1% (adjusted odds ratio, 0.6; 95% CI, 0.46 to 0.77; P< 0.0001). Additionally, the rate of ICU transfer increased from 85.4% to 92.1% (risk difference, 6.7; 95% CI, 7.6 to 5.8; P< 0.0001) after implementing the RRRS.Conclusion: Implementing the RRRS is associated with a reduction in in-hospital mortality and the incidence of CPR outside the ICU.Keywords: rapid response system, rapid response team, deteriorating patient, in-hospital mortality, cardiopulmonary resuscitation, intensive care unit, implementation protocol